Two enigmatic ridges in the Pantelleria Vecchia Bank (NW Sicilian Channel). Issue 3 (March 2023) - Lodolo, Emanuele; Nannini, Paolo; Baradello, Luca; Ben-Avraham, Zvi
Abstract: The Pantelleria Vecchia Bank is a submerged calcareous-arenitic shoal in the NW sector of the Sicilian Channel. Together with other morphological heights, some of which are volcanic in origin, this shoal punctuates the shallow Adventure Plateau, which was above sea level from the Last Glacial Maximum until at least 9000 years ago. The rise in sea level caused by the melting of the ice caps gradually flooded the plateau, isolating the heights and creating a broad archipelago until the area was finally submerged. High-resolution Multibeam bathymetric mapping shows that the Pantelleria Vecchia Bank has an 820 m long rectilinear ridge connecting the two main shoals of the bank, and an 82 m long ridge perpendicular to the 820 m ridge 100 m from its southern end. The top of the 820 m ridge lies in a water depth of 35 m, its base in about 42 m, and the seaward side has a fairly uniform slope of 16°–22°. The 82 m ridge has an average width of ∼7 m and rises ∼1 m above the surrounding seafloor. Underwater photographs document that the entire seaward side of the 820 m ridge consists of juxtaposed blocks, the largest measuring about 3 × 4 m, some of which are rectangular in shape, while the upper part consists of horizontally arranged blocks and the lower part of sub-vertical blocks embedded in the sediments. Petrographic analyses show that the blocks forming the seaward side of the 820 m ridge can be classified as late Pleistocene calcirudites, while the 82 m ridge consists of bioclastic calcarenites of Tortonian age. A series of high-resolution seismic profiles crossing both ridges and composite mosaics of the seafloor obtained from underwater videos provide a comprehensive panorama of these two peculiar and in many ways enigmatic structures. The structures described and the palaeogeographical context in which they are embedded do not exclude the possibility that they are artefacts indicating an ancient temporary or permanent human presence in the Pantelleria Vecchia Bank.